Induction of callus and adventitious shoots on epicotyl and hypocotyl segments of cumaru (Dipteryx odorata) - Sampaio, Paulo Tarso Barbosa; Jardim, Lyana Silva; Blind, Ariel Dotto; Bruno, Flavio Mauro Souza (Federal University of Piauí, 2018)
Somatic embryogenesis from callus induced in epicotyl and hypocotyl segments can be viable native species in order to better -benefit ratio costs, and rates of clonal multiplication. In this sense, two trials were established to induce callus and adventitious buds on hypocotyl and epicotyl segments of cumaru bean seedlings germinated in vitro in different concentrations and combinations of growth regulators. At first, we used the MS medium supplementwith ANA (0.0, 1.5 mg.L-1) and TDZ (0.0, 4.0 and 8.0 mg.L-1) distributed in factorial 2 x 3 x 2 (x auxin cytokinin x explant) with eight replications. In the second, it was used the WPM medium supplemented with BAP (2.0 mg L-1) and plus 2,4-D (2.0 and 4.0 mg L-1) in a factorial 2 x 2 (auxin x explant) with 15 repetitions each. They were evaluating callus formation and the average number of adventitious shoots during the period of 90 days. The results indicated that the highest average for callus formation was observed when the explants were subjected to concentrations of 8.0 mg L-1 TDZ combined with 1.5 mg L-1 ANA in MS medium. For the formation of buds, the WPM medium plus 2.0 mg L-1 2,4-D in the second experiment, induced higher number of shoots, being significant the use of auxin, and its interaction with the type of explant.